Reading Scripture with the church : towards a hermeneutic for theological interpretation - Adam, A.K.M. (Andrew Keith Malcolm), 1957; Fowl, Stephen E.; Vanhoozer, Kevin J.; Watson, Francis (Grand Rapids, Michigan : Baker Academic, 2006)
In Reading Scripture with the Church, four leading biblical scholars set forth constructive theological approaches to biblical interpretation.
Toward a resolution yet to be revealed / A.K.M. Adam.
Includes bibliographical references and indexes
Keywords: Bible -- Hermeneutics; Bible -- Criticism, interpretation, etc